1976
DOI: 10.1113/expphysiol.1976.sp002342
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vasopressin Upon the Excretion of Calcium by the Sheep

Abstract: Vasopressin (140 ,U/min) was infused intravenously into 12 conscious merino ewes for 2 hr. Urine flow rate and free water clearance were consistently reduced. There was no effect upon renal plasma flow, glomerular filtration rate or the rate of excretion of sodium, potassium, magnesium, chloride or phosphate. Although all animals received 75 mmol calcium chloride into the rumen on the previous day, five commenced the experiment with calcium excretion rates of less than 1 ,umol/min. In these, vasopressin furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…When this phenomenon was investigated in water-loaded sheep using hormone dose rates closer to 'physiological' than those of the previous authors, Kuhn (1966) found that antidiuresis produced by the administration of vasopressin or oxytocin was always associated with significant decreases in renal calcium excretion whereas Beal, Clark, Cross & French (1976) reported significant decreases in excretion after vasopressin only in sheep with calcium excretion rates less than 1 #smole/min. At higher rates of calcium excretion, vasopressin infusion did not alter calcium excretion although antidiuresis still occurred.…”
Section: Introductionmentioning
confidence: 96%
“…When this phenomenon was investigated in water-loaded sheep using hormone dose rates closer to 'physiological' than those of the previous authors, Kuhn (1966) found that antidiuresis produced by the administration of vasopressin or oxytocin was always associated with significant decreases in renal calcium excretion whereas Beal, Clark, Cross & French (1976) reported significant decreases in excretion after vasopressin only in sheep with calcium excretion rates less than 1 #smole/min. At higher rates of calcium excretion, vasopressin infusion did not alter calcium excretion although antidiuresis still occurred.…”
Section: Introductionmentioning
confidence: 96%